2010
DOI: 10.1530/eje-09-0706
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the PPARγ agonist rosiglitazone downregulates interleukin-1 receptor antagonist in individuals with metabolic syndrome

Abstract: Objectives: Thiazolidinediones (TZDs) reduce insulin resistance, but also have pleiotropic properties including effects on inflammation. The balance between protective and proatherogenic effects may differ in various patient populations. We studied the effect of rosiglitazone on inflammatory markers in patients with metabolic syndrome (MetSyn). Methods: In a cross-over randomized controlled trial, 23 subjects with MetSyn were assigned to treatment with rosiglitazone that was uptitrated from 4 mg/day for 6 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…In a recent study IL-1Ra was even identified as a novel biomarker for clinically incident diabetes, over and above the classical risk factors such as BMI and waist: hip ratio [18]. Supporting a possible role in the development of insulin resistance, thiazolidinedione (TZD) treatment significantly reduced levels of IL-1Ra in patients with metabolic syndrome [19], as well as in cell culture studies where TZDs inhibited the production of IL-1Ra from proinflammatory adipocytes [20].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study IL-1Ra was even identified as a novel biomarker for clinically incident diabetes, over and above the classical risk factors such as BMI and waist: hip ratio [18]. Supporting a possible role in the development of insulin resistance, thiazolidinedione (TZD) treatment significantly reduced levels of IL-1Ra in patients with metabolic syndrome [19], as well as in cell culture studies where TZDs inhibited the production of IL-1Ra from proinflammatory adipocytes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our findings do not exclude the possibility of an interaction in subgroups, and SUA and adiponectin may act synergistically with regard to more advanced stages of CKD [58][59][60], and in subjects with less favourable values of SUA, adiponectin and the urinary biomarkers. This matter is of relevance since pharmaceutical agents such as PPAR γ agonists [21,22] and some blockers of the renin-angiotensin system [61,62] are known to simultaneously decrease SUA and increase adiponectin, and thus these biomarkers may share common pathways. Therefore, this issue should be addressed further through longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers have shown significant negative correlation [17], but not in all cohorts [18]. Pharmaceutical agents such as peroxisome proliferator-activated receptor-ɣ (PPAR ɣ) agonists and xanthine oxidase inhibitors [19,20] have been demonstrated to simultaneously decrease SUA and increase adiponectin [21,22]. Thus, it may be suggested that the two biomarkers share some common pathways.…”
Section: Introductionmentioning
confidence: 99%
“…antidiabetic medication, including thiazolidinediones [85 ], incretin mimetics [86 ], metformin [83,84], the alpha-glucosidase inhibitors acarbose [87] and voglibose [88 ], and omega-3 fatty acids [89 ], have generated interest in the treatment of the metabolic syndrome. Although thiazolidinediones reduce insulin resistance, their effect on inflammatory pathways seems complex and has not yet been fully elucidated [85 ].…”
Section: D: Diabetes Preventionmentioning
confidence: 99%
“…Although thiazolidinediones reduce insulin resistance, their effect on inflammatory pathways seems complex and has not yet been fully elucidated [85 ]. Bhushan et al [86 ] performed a retrospective analysis of glycemic control and cardiometabolic risk factors in 176 patients treated with exanetide, an incretin mimetic.…”
Section: D: Diabetes Preventionmentioning
confidence: 99%